2014
DOI: 10.1016/j.tins.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A de novo convergence of autism genetics and molecular neuroscience

Abstract: Autism spectrum disorder (ASD) and intellectual disability (ID) are neurodevelopmental disorders with large genetic components, but identification of pathogenic genes has proceeded slowly because hundreds of loci are involved. New exome sequencing technology has identified novel rare variants and has found that sporadic cases of ASD/ID are enriched for disruptive de novo mutations. Targeted large-scale resequencing studies have confirmed the significance of specific loci, including chromodomain helicase DNA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
361
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(373 citation statements)
references
References 91 publications
(116 reference statements)
10
361
0
2
Order By: Relevance
“…ASD affect 1 of 45 children according to the most recent estimates (Zablotsky, Black, Maenner, Schieve, & Blumberg, 2015), and remain mechanistically poorly understood. However, because a notable fraction of candidate genes relate to synaptic transmission (Persico & Napolioni, 2013; Krumm, O'Roak, Shendure, & Eichler, 2014), ASD are typically perceived as a system‐level condition, which gave rise to many functional magnetic resonance imaging (fMRI) studies attempting to decipher how the autistic brain works.…”
Section: Introductionmentioning
confidence: 99%
“…ASD affect 1 of 45 children according to the most recent estimates (Zablotsky, Black, Maenner, Schieve, & Blumberg, 2015), and remain mechanistically poorly understood. However, because a notable fraction of candidate genes relate to synaptic transmission (Persico & Napolioni, 2013; Krumm, O'Roak, Shendure, & Eichler, 2014), ASD are typically perceived as a system‐level condition, which gave rise to many functional magnetic resonance imaging (fMRI) studies attempting to decipher how the autistic brain works.…”
Section: Introductionmentioning
confidence: 99%
“…Other modes of inheritance consistent with sporadic disorder are autosomal recessive, X-linked, and imprinting, and examples of all of these are also found for severe ID (des Portes 2013; Musante and Ropers 2014;Buiting 2010). Recently, sequencing of probands and parents has confirmed that single de novo protein-altering mutations are also causal in a significant proportion of cases (Gilissen et al 2014;Krumm et al 2014;Veltman and Brunner 2012). ID sometimes occurs in the context of a syndromic disorder, in which there are co-occurring developmental defects in other organs (van Bokhoven 2011).…”
Section: Intellectual Disability and Autism Spectrum Disordersmentioning
confidence: 99%
“…Gene-disrupting mutations (nonsense, splice site, and frame shifts) are twice in affected versus unaffected children and have far more impacts on the individual [19]. These studies suggest that protein-truncating de novo SNVs contribute to the risk of ASD for about 10%-15% of probands [20]. The burden of de novo mutations affecting genes expressed in the brain is higher in individuals with ASD as compared with controls [3].…”
Section: Rare Single-gene Mutations In Asdmentioning
confidence: 99%
“…Third, due to exome capture limitations or errors in the reference genome, the coverage of genomic regions is incomplete. Fourth, mutation calls are made from only coding regions, and therefore, noncoding regions are missed that might affect RNA expression or processing [19][20][21].…”
Section: Rare Single-gene Mutations In Asdmentioning
confidence: 99%